EFEK TRANSOM-NONTRANSOM KAPAL PADA DISTRIBUSI GELOMBANG MEDAN JAUH MELALUI PENDEKATAN CFD - Daffa Nurpradana, (2021)
Ship is the union of its construction from the bow to the stern. Commonly the bodies shape of ship can be divided into some aspect even to its stern. The Ship Engineer must calculate and predict how ship stern will affect on its hydrodynamics when sailing efficiently and safe. In general, the shape of stern on ship divided into two kind, Transom and Non Transom. This Thesis is about research to compare between two kind of stern to calculate its resistance value. To find the value from the comparison, the research will depends on Ansys CFD. This research will use Workboats as its Model and transform it into two Transom models with different D/T and one Non Transom Model. The result of CFD simulation will compare the value of resistance as Ct, Cv, Cw. The Result of calculations will take the Transom Stern have the lower value of resistance than Non Transom Stern and the wake its generate have more reasonable pattern and linear.